Community Portrait : St. Léonard - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Community Portrait : Laval - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2012-2013 : Quebec's English-speaking Community Networks and their Partners in Public Health and Social Services - Pocock, Joanne (Community Health and Social Services Network, 2013)
The 2012-2013 BDR reports unpon the nature and development of the partnerships that CHSSN Networking and Partnership Initiative (NPI) networks have established in their regions. The report represents the experience, thoughts, and observations - the collective wisdom - of the NPI networks on a range of topics related to their partnerships. The report looks back at the work incolved in partnering since the genesis of CHSSN, the ongoing challenges and successes, and the perceived impact of partnering on the NPI communities and their access to health and social services in English.
Keywords: Official Language Minority Community (OLMC)

Improving Access to Health and Social Services for Quebec’s English-speaking Population : Development Priorities 2013-2018 - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This report has been prepared at the request of the Community Health and Social Services Network (CHSSN). It is intended for presentation to Health Canada in the context of the renewal of the Federal Government’s commitments to official language minority communities (OLMCs) for the period 2013-2018. The report presents development priorities for the improvement of access to health and social services in English for Quebec’s English-speaking communities as identified by the personnel of organizations work- ing on this issue.

Improving Access to Health and Social Services for Quebec’s English-speaking Population: Development Priorities 2013-2018 : A Companion Document - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This document has been prepared at the request of the Community Health and Social Service Network (CHSSN). It is the companion document to Improving Access to Health and Social Services for Quebec’s English- Speaking Population, Development Priorities 2013-2018, also prepared at the request of the CHSSN. Both are intended for presentation to Health Canada in the context of the renewal of the Federal Government’s com- mitments to official linguistic minorities for the period 2013-2018. These commitments have been funded to date under the Roadmap for Canada’s Linguistic Duality 2008-2013 (the Roadmap). More about the context of the project is presented in Appendix I.